Taking action to secure a healthy future for all. (2nd April 2020) - Ranmal, Rita; Elwell-Sutton, Tim
Abstract : In this article, Rita Ranmal and Tim Elwell-Sutton look at recent trends in population health, the conditions needed for healthy lives and some effective actions that can be taken to secure the public's health in the long term